Akkermansia muciniphila-Nlrp3 is involved in the neuroprotection of phosphoglycerate mutase 5 deficiency in traumatic brain injury mice - Chen, Yuhua; Chen, Junhui; Wei, Hong; Gong, Kai; Meng, Jiao; Long, Tianlin; Guo, Jianfeng; Hong, Jun; Yang, Lingjian; Qiu, Junling; Xiong, Kun; Wang, Zhanxiang; et al. (Frontiers in Immunology, 2023)
Introduction Gut-microbiota-brain axis is a potential treatment to decrease the risk of chronic traumatic encephalopathy following traumatic brain injury (TBI). Phosphoglycerate mutase 5 (PGAM5), a mitochondrial serine/threonine protein phosphatase, resides in mitochondrial membrane and regulates mitochondrial homeostasis and metabolism. Mitochondria mediates intestinal barrier and gut microbiome. Objectives This study investigated the association between PGAM5 and gut microbiota in mice with TBI. Methods The controlled cortical impact injury was established in mice with genetically-ablated Pgam5 (Pgam5−/−) or wild type, and WT male mice were treated with fecal microbiota transplantation (FMT) from male Pgam5−/− mice or Akkermansia muciniphila (A. muciniphila). Then the gut microbiota abundance, blood metabolites, neurological function, and nerve injury were detected. Results Treated with antibiotics for suppressing gut microbiota in Pgam5−/− mice partially relieved the role of Pgam5 deficiency in the improvement of initial inflammatory factors and motor dysfunction post-TBI. Pgam5 knockout exhibited an increased abundance of A. muciniphila in mice. FMT from male Pgam5−/− mice enabled better maintenance of amino acid metabolism and peripherial environment than that in TBI-vehicle mice, which suppressed neuroinflammation and improved neurological deficits, and A. muciniphila was negatively associated with intestinal mucosal injury and neuroinflammation post-TBI. Moreover, A. muciniphila treatment ameliorated neuroinflammation and nerve injury by regulating Nlrp3 inflammasome activation in cerebral cortex with TBI. Conclusion Thus, the present study provides evidence that Pgam5 is involved in gut microbiota-mediated neuroinflammation and nerve injury, with A. muciniphila-Nlrp3 contributing to peripheral effects.